Cultivation of Grit in Nursing Students: A Qualitative Descriptive Study “Cultivation of Grit” - Carolyn Spriggs Muchna PhD (SAGE Open Nursing)
Background Predicted nursing deficits and low nursing student retention rates highlighted the need to investigate cultivation of grit, a malleable trait involving perseverance and passion to achieve long-term goals amidst challenges and difficulties. Objective The objective of this study was to identify how cultivation of grit and additional academic and non-academic strategies aided gritty second-year associate degree-seeking nursing students in addressing nursing program challenges and completing their nursing program. Methods Twenty-two second-year associate degree-seeking nursing students in rural central Arizona completed demographic and Grit-O Scale questions using Survey Monkey™ and participated in semi-structured interviews or focus group discussions held from September through December 2022. Research questions provided study foundation: RQ1: How do second-year nursing students with high levels of self-perceived grit of greater than 3.5 out of 5 as measured on the Grit-O Scale describe how grit was cultivated during their associate degree-seeking nursing program? RQ2: How do second-year nursing students with high levels of self-perceived grit describe how additional academic and non-academic strategies added to them in dealing with the challenges of their associate degree-seeking nursing program? Design Qualitative Descriptive Research Results Inductive thematic analysis revealed six themes: importance of perseverance and passion, facets of grit; identification of program challenges and strategies used to deal with challenges; and the significance of support from nursing cohort, family, and friends, and nursing instructors. Conclusions Effective strategies for participating nursing student retention and program completion involved cultivation of grit and its facets of perseverance and passion and additional academic and non-academic strategies of nursing cohort and instructor support aided students in dealing with challenges faced during their associate degree-seeking nursing program at a rural, central Arizonan community college.